Learning from failed supply chains: the application of complex adaptive systems and a modified SAFE framework in evaluating proposed system improvements. (1st January 2013) - Fizzanty, Trina; Russell, Iean; Collins, Ray
This paper developed a framework for evaluating and improving failed supply chains, based on two case studies set in the mango industry of Indonesia, a developing country. It analysed the cases from a complex adaptive systems (CAS) perspective and applies a sustainability, acceptability, feasibility, efficiency (SAFE) framework. The paper also identified issues relevant to supply chain sustainability in a developing country context. Improvements were suggested from the identification of system-level leverage points through a process of cross case analysis, supported by interviews and consensus-seeking focus groups with multiple stakeholders. Using a modified SAFE framework, proposals for system improvements were identified for setting-up the system, measuring system performance, and establishing the behaviours of the system. Lessons learned from these two cases of supply chain failure centred on increasing learning capacity, establishing commitment among stakeholders and lowering the resistance of the system environment.